New packet header support and key exchange mechanism for secure trivial file transfer protocol / Nur Nabila Mohamed ...[et al.] - Mohamed, Nur Nabila; Mohd Yussoff, Yusnani; Kamarudin, Nazhatul Hafizah; Hashim, Habibah (UiTM Press, 2017)
- TFTP has received a significant demand in recent years because of its lightweight feature and compatibility on limited low-level embedded system. Nevertheless, as it provides no security mechanism, questions have been raised about the safety issue especially during data collection and during system update. Despite the vulnerability matter, there is also a concern to integrate TFTP with a suitable and compatible security mechanism. Because TFTP is a lightweight protocol, the proposed security mechanism should also be simple yet powerful to protect the file transmission process against any attack. The first important method in securing the TFTP communication is to verify the new packet header that can support the key exchange operation for the next encryption process. DHKE, a general and popular key exchange mechanism usually be chosen but it is vulnerable to MITM attack. Therefore, in this work, a new DHKE-based key exchange technique is proposed to be integrated with TFTP packet header for security support which is expected to provide a secure TFTP communication in the future M2M technology.